A comparative study of cryodamages of boar spermatozoa frozen with conventional liquid nitrogen vapour freezing method - BAISHYA, S K; BISWAS, R K; KADIRVEL, G; DEKA, B C; KUMAR, SURESH; THAKURIA, D R (The Indian Journal of Animal Sciences, 2014)
The objective of the present study was to quantify the various cryodamages that boar spermatozoa undergo following freezing with conventional liquid nitrogen vapour freezing method. Sperm-rich fractions of ejaculates (15) collected from 6 boars were utilized for the study. The sperm parameters included for investigating the cryodamages were motile spermatozoa, live spermatozoa, live intact acrosome, plasma membrane intact spermatozoa, HOST-reacted spermatozoa, live spermatozoa with high mitochondrial membrane potential, lipid peroxidised spermatozoa and DNA-damaged spermatozoa. The results showed that the process of freezing significantly decreased per cent motile spermatozoa, live spermatozoa, live intact acrosome, plasma membrane intact spermatozoa, HOST- reacted spermatozoa and mitochondrial membrane potential of live sperm population, while increased per cent lipid peroxidised spermatozoa and DNA-damaged spermatozoa. The extent of cryodamage recorded in respect of motile spermatozoa, live spermatozoa, live intact acrosome, plasma membrane intact spermatozoa, HOST-reacted spermatozoa, live spermatozoa with high mitochondrial membrane potential obtained after freezing was 40.33, 34.87, 35.02, 39.48, 39.17 and 6.72 % respectively. The level of cryodamage in the form of lipid peroxidised spermatozoa and DNA-damaged spermatozoa were 8.00 and 3.06 % respectively. In conclusion, the detrimental effect of cryodamage associated with conventional liquid nitrogen vapour freezing was more pronounced on sperm motility, viability, acrosome integrity and plasma membrane integrity than on sperm mitochondrial membrane potential and membrane lipid, while its effect was minimal on sperm DNA.